Children in the performing arts: conversation with Meredith Monk (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
In this interview, the American artist Meredith Monk talks about her path in the performing arts and, more specifically, the participation of children in her works. Monk also addresses topics such as Buddhism, the artist's choices and paths, the live arts, aging and the notions of tradition and legacy.
Keywords: Meredith Monk; Performing arts; Children; Art